Performance Efficiency of Islamic Banks in Pakistan: An Application of CAMEL Model - ABDUL WASAI; DR. SHAMS-UR-RAHMAN; AAMIR KHAN (Journal of Business & Tourism, 2021)
This paper aims at evaluating the soundness of Islamic banks working in Pakistan for the period 2008 to 2015. The current study comprises of five full fledge Islamic banks, actively working in Pakistan. The study applied CAMEL parameters to achieve its purpose. It has utilized capital adequacy, Asset quality, Management ability, Earnings ability and liquidity ratios of selected banks. The findings of the study show that although Islamic banks in Pakistan have adequate capital, yet they have limited asset management ability and substandard earnings ability during the selected time period. The study also depicted that Islamic banks have high degree of liquidity thus enjoying low bankruptcy risk. The findings of this study is of prime interest for the management and shareholders of the selected banks. On one hand, the results of this study provide an insight into the performance of these banks. On the other hand, the results also contain useful information for managers and policy makers as they could find and correct easily, the weak areas of their respective institutions.